Morphological Diversity And Molecular Characterization Of Macrophomina Phaseolina Causing Stem Canker Of Pigeonpea In North Eastern Karnataka (Journal of Plant Disease Sciences, 2018)
Macrophomina Stem Canker caused by Macrophomina phaseolina is an emerging disease in pigeonpea. Fifty two isolates of M. phaseolina were collected from different regions from North Eastern parts of Karnataka. All the 52 M. phaseolina isolates were pathogenic to pigeonpea proved by modified cello-tape method. Isolates were characterized based on morphological features viz., colour, texture, mycelium, sclerotia and micro-sclerotia and categorized in to three groups. Among 52 isolates, nine isolates produced both sclerotia and micro-sclerotia under PDA and water agar respectively. Twenty nine isolates did not produce any sclerotia and micro-sclerotia. Twenty two isolates were selected based on geographical representation and morphological features for the amplification of the DNA using ITS primers (ITS 1 + ITS 4) which showed a 550 to 600 bp and sequences were deposited with accession no. KJ629071-KJ629093 at NCBI, GenBank, Mary land, USA. The phylogenetic tree based on rDNA-ITS analysis showed that the minimum number of M. phaseolina isolates were very diverse. Thus, the study was found useful for revealing the morphological diversity of within the pigeonpea growing areas of Karnataka.
Keywords: Macrophomina Stem Canker (MSC); Macrophomina phaseolina; morphological variability; ITS primers; rDNA; phylogenetic tree R